Case Report and Literature Review of Insulinoma in the Geriatric Population: An 86-Year-Old Female with Syncope of Unknown Origin. (18th July 2020) - Eichelberger, Gerry Samantha; Carbono, Jordan; Field, Zachary; Kainaur, KanwarAnoop; Montalvo, Federico
Abstract : Insulinomas are extremely rare pancreatic endocrine tumors. The tumor is characterized by endogenous hypersecretion of insulin and ensuing development of symptoms of neuroglycopenia and the catecholaminergic response. Symptoms may not always be present, particularly in patients compensating appropriately with increased appetites and caloric intake due to low glucose levels. Early localization of the disease is essential to prevent lethal hypoglycemia and timely treatment. This case report and literature review depict the case of a pancreatic insulinoma in an 86-year-old female, an exceptionally rare presentation based on age and absence of clinical symptoms for one or more years prior to hospitalization. Despite its rarity, similar presentations have been reported in the literature and are further outlined with characteristics and treatment plans. This case highlights a unique presentation of insulinoma and suggests the need for clinical vigilance and further study. It also discusses diagnosis, localization, and management of this uncommon disease in patients above the age of seventy-five.